Dynamic study of small toxic hydrophobic proteins PepA1 and PepG1 of Staphylococcus aureus - Sur, Vishma Pratap; Simonik, Ondrej; Novotna, Michaela; Mazumdar, Aninda; Liska, Frantisek; Vimberg, Vladimir; Komrskova, Katerina (International journal of biological macromolecules, 2022)
Toxin-antitoxin (TA) systems are small genetic elements which encode toxin proteins that interfere with vital cellular functions. PepA1 and PepG1 toxin proteins, known also as SprA1 and SprG1, are type I TA. In Staphylococcus aureus (S. aureus), their expression without the antitoxin counterparts (SprA1AS and SprF1), is lethal to the pathogen. Molecular Dynamics (MD) simulation was performed for PepA1 and PepG1 to understand their dynamic state, conformational changes, and their toxicity. The protein structures were constructed and used for MD simulation and the conformational changes, stability, flexibility, fluctuations, hydrophobicity, and role of their dynamic state on function prediction were studied extensively by GROMACS MD simulation analysis tools. In silico study indicated that the PepA1 and PepG1 proteins change their structural conformation from an open to closed state where PepA1 conformational changes were faster (10 ns) than PepG1 (20 ns) while PepG1 exerted more stability and flexibility than PepA1. According to SASA values, PepG1 is more hydrophobic than the PepA1 and forms fewer hydrogen bonds than PepA1. The in vivo study with PepA1 and PepG1 proteins provided evidence that both the conformation changes between the open and closed states and the amino acid sequence are crucial for peptide toxicity.
Keywords: Antitoxins; Peptides; lidé; peptidy; Toxin-antitoxin system; Bacterial Proteins; Cloning; stafylokokové infekce; Hydrophobic and Hydrophilic Interactions; bakteriální proteiny; hydrofobní a hydrofilní interakce; Staphylococcal Infections; antitoxiny; Molecular dynamics simulation; PepA1; Humans; PepG1; Staphylococcus aureus